IS YOUR HR DEPARTMENT OBSOLETE? REDEFINING PEOPLE OPERATIONS FOR THE 21ST CENTURY - Tika Zulhiani; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
This article examines the critical imperative for organizations to transform their traditional Human Resources (HR) function into a strategic, modern People Operations model. The background establishes that in a knowledge-based economy where human capital is the primary driver of value, administrative and reactive HR practices create a strategic liability. The objective is to provide a diagnostic framework and a practical roadmap for this essential evolution. The methodology involves a synthesis of contemporary management literature, organizational case studies, and analysis of emerging best practices in talent strategy and employee experience. The results detail the four foundational pillars of a modern People function—Strategic Partnership, Employee Experience as a Product, Data-Driven Decisions, and Culture Cultivation—and a six-step transformation roadmap. The discussion argues that this shift moves HR from a cost center to a core competitive advantage. The conclusion asserts that redefining people operations is not a choice but a strategic necessity for organizational resilience and growth.